Status and specificity of ethnic mythology at the present stage of socio-cultural development: social and philosophical analysis - Kurbacheva, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article is devoted to the social and philosophical understanding of the essence and role of ethnic mythology at the present stage of socio-cultural development. The relevance of the work is dictated, on the one hand, by the escalating of ethno-cultural tension and the increasing mythologisation of history, on the other hand, by the shortage of comprehensive and systematic studies of the problems of ethnic myth-making in the context of modern conflicts. The article proposes a substantive philosophical analysis of the essence of ethnic myths, revealing their typological diversity and dynamic character, as well as the specific differences between modern and classical ethnic miths. The author emphasises that modern ethnic mythology is a specific type of constructed social knowledge that goes through certain stages of its formation. As a result, today ethnic mith is understood as a symbolic narrative that accumulates and interiorises the socio-cultural experience of an ethnic community in specific historical conditions. The article highlights the importance of ethnic mythology in the study of ethnic identity. The myths reflect the key features of ethnic self-consciousness, its main symbols and images, in which are manifested the specifics of awareness of one’s community and attitude towards others communities. The author draws attention to the practical significance of the study of ethnic mythology: firstly, the exaggerated mythologisation of history and culture often serves as an indicator of potential ethno-cultural tension in society, and secondly, ethnic myth can be used in the construction of a national idea or the formation of a country’s image, which determines not only relevance, but also the complexity of the topic under study.